2013
DOI: 10.1177/0305735613501938
|View full text |Cite
|
Sign up to set email alerts
|

Moody melodies: Do they cheer us up? A study of the effect of sad music on mood

Abstract: Despite the paradox inherent in the idea that sad music could make people happier, research indicates that an improved mood is amongst the primary motivations that people give for listening to sad music. However, it is not clear whether listeners are always able to achieve such aims. This article reports a study in which 335 participants listened to a piece of self-selected sad music. Before and aftermeasures of mood were taken, and participants also completed psychometric scales of rumination, absorption and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
78
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 37 publications
8
78
2
1
Order By: Relevance
“…We hypothesized that these young people more often lived in an adverse social context and had personality characteristics that not only enhanced detecting sadness in music, but also induced or strengthened their sad mood when listening to it. Our results showed that adolescents who reported elevated levels of depressive mood were most negatively affected by listening to sad music, corroborating earlier findings among Australian secondary school and university students (Garrido & Schubert, 2015a, 2015b a M0, null model; M1, model with background characteristics (gender and education); M2: model with background characteristics and social context (negative family climate and bullied by peers); M3, model with background characteristics and personality (anxious/depressed, negative social comparison and self-esteem); and M4, model with background characteristics, social context and personality. Saarikallio, 2014;McFerran et al, 2015), adding to the existing evidence that self-selected and self-identified sad music's negative effects on depressed young people may be universal.…”
Section: Discussionsupporting
confidence: 91%
“…We hypothesized that these young people more often lived in an adverse social context and had personality characteristics that not only enhanced detecting sadness in music, but also induced or strengthened their sad mood when listening to it. Our results showed that adolescents who reported elevated levels of depressive mood were most negatively affected by listening to sad music, corroborating earlier findings among Australian secondary school and university students (Garrido & Schubert, 2015a, 2015b a M0, null model; M1, model with background characteristics (gender and education); M2: model with background characteristics and social context (negative family climate and bullied by peers); M3, model with background characteristics and personality (anxious/depressed, negative social comparison and self-esteem); and M4, model with background characteristics, social context and personality. Saarikallio, 2014;McFerran et al, 2015), adding to the existing evidence that self-selected and self-identified sad music's negative effects on depressed young people may be universal.…”
Section: Discussionsupporting
confidence: 91%
“…This replicates the findings of Garrido and Schubert (2013b). The hypothesis was supported by the data, with high ruminators expe riencing significant increases in depressed mood as measured by the POMS after listening to their selfselected YouTube video.…”
Section: Discussionsupporting
confidence: 84%
“…In line with this view, pieces that are perceived to sound sad also tend to be judged as beautiful (Eerola & Vuoskoski, 2010), and exposure to sad sounding music can improve sad mood states (Tsai, Chen, & Tsai, 2014;van den Tol & Edwards, 2014). Conflicting evidence emerges from behavioral and physiological studies, however, which often report that listening to sad sounding music does indeed induce negative emotions (e.g., Blood et al , 1999;Garrido & Schubert, 2015;Green et al, 2008;Juslin, Liljeström, Laukka, Västfjäll, & Lundqvist, 2011;Mitterschiffthaler, Fu, Dalton, Andrew, & Williams, 2007;Vuoskoski et al, 2012). Huron (2011) argues that sad sounding music induces genuine sadness accompanied by elevated levels of prolactin, a hormone that is associated with comfort and consolation, and released during episodes of sadness.…”
Section: Liking Sad Sounding Musicmentioning
confidence: 99%